Correlated ignition delay expression of two-stage ignition fuels for Livengood-Wu model-based knock prediction. (15th January 2020) - Song, Hwasup; Song, Han Ho
Highlights: Autoignition predictability for two-stage ignition fuels improved by 4 CADs. Proper quantification of the low-temperature chemistry progress in a modern engine. An empirical method for a simple and accurate autoignition prediction proposed. Evaluation of temperature-pressure trajectories using a rapid compression machine. Abstract: In this study, an alternative scheme improving the Livengood-Wu model-based knock predictability for downsized and boosted spark-ignition (SI) engines with two-stage ignition fuels is proposed by introducing a newly corrected ignition delay correlation applicable to two-stage ignition fuels. While there is little chance of cool-flame heat release realized within the in-cylinder mixture under certain knock-prone operations, the effect of unnecessarily accounted cool-flame exothermicity to the Livengood-Wu integration process and the eventual overestimation error is found to be as large as 2-4 crank angle degrees (CADs) on the knock timing, which could limit the potential workability and the benefits of the downsizing with boost strategy. This correlation is also useful for mapping the ignition delay domain of two-stage ignition fuels without their cool-flame heat release that is subject to the relevant pressure-temperature trajectories of the engine unburned gas, and rapid compression machine (RCM) experiments are conducted to reproduce the unburned gas behavior of a boosted SI engine.